Trends in Immune Cell Function Assay and Donor‐Specific HLA Antibodies in Kidney Transplantation: A 3‐Year Prospective Study. Issue 12 (30th October 2013) - Libri, I.; Gnappi, E.; Zanelli, P.; Reina, M.; Giuliodori, S.; Vaglio, A.; Palmisano, A.; Buzio, C.; Riva, G.; Barozzi, P.; Luppi, M.; Cravedi, P.; et al.
Abstract The immune cell function assay (ICFA) and de novo anti‐donor‐specific HLA antibodies (DSA) have been proposed as assays for immune monitoring in renal transplantation, but longitudinal studies examining the modification of both parameters over time and their relation with clinical events are lacking. We prospectively measured longitudinal changes in ICFA and DSA levels in 55 kidney transplant recipients over 3‐year follow‐up (534 visits) and analyzed their relation with the risk of developing acute rejections or infections. Seven patients (12.7%) developed biopsy‐proven acute rejection, and 20 (36.4%) developed viral infections. At 3 years posttransplant, 28% of the patients had developed de novo DSA. ICFA levels peaked at 1–2 months posttransplant (p = 0.005) and leveled off thereafter. They were not associated with the risk of acute rejections, viral infections or development of de novo DSA. Instead, the incidence of de novo DSA was higher in patients who previously had viral infections (adjusted‐odds ratio of de novo DSA associated with prior infections: 6.03 [95% CI, 1.64–22.06; p = 0.007]). Our prospective, longitudinal study does not support using ICFA to quantify the immune risk in kidney transplantation. Further studies are needed to confirm the relationship between viral infections and the subsequent development of de novo DSA.